APPLICATION OF THE WORD SQUARE LEARNING MODEL TO IMPROVE STUDENTS’ LEARNING ACTIVITY AND LEARNING OUTCOMES AT SMAN 11 PANGKEP - Maksar, Adie; Annas, Suwardi; Devilla, Rego (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Nowadays, the teacher should be professional to be able to cultivate varied learning models for every learning subject so that students are not saturated while following the learning process. This paper discusses the improvement of students’ learning activity and learning outcomes through a word square learning model at SMA Negeri 11 Pangkep. It is a classroom action research (PTK). The research subjects involved 33 class XI students. Data collection techniques are carried out through observation, tests, and documentation. Data analysis techniques use descriptive analysis. The results indicate that 1) the percentage of students’ learning activity increased each cycle wherein in the first cycle students’ learning activity is in the less active category and increases in cycle II in the very active category. In addition, 2) the completeness of students’ learning outcomes increases every cycle wherein in cycle I it was 33% with an average learning outcome of 66.9 and increases in cycle II at 81% with an average student learning outcome of 85.7. Thus, the application of the word square learning model can increase the activeness and learning outcomes of economics subjects for class XI students at SMA Negeri 11 Pangkep.